Bronchopulmonary dysplasia in extremely premature infant with congenital lobar emphysema: a case report - Bingchun Lin; Huitao Li; Chuanzhong Yang (BMC, 2021)
Abstract Background Congenital lobar emphysema (CLE) is a congenital pulmonary cystic disease, characterized by overinflation of the pulmonary lobe and compression of the surrounding areas. Most patients with symptoms need an urgent surgical intervention. Caution and alertness for CLE is required in cases of local emphysema on chest X-ray images of extremely premature infants with bronchopulmonary dysplasia (BPD). Case presentation Here, we report a case of premature infant with 27 + 4 weeks of gestational age who suddenly presented with severe respiratory distress at 60 days after birth. Chest X-ray and computed tomography (CT) indicated emphysema in the middle lobe of the right lung. The diagnosis of CLE was confirmed by histopathological examinations. Conclusions Although extremely premature infants have high-risk factors of bronchopulmonary dysplasia due to their small gestational age, alertness for CLE is necessary if local emphysema is present. Timely pulmonary CT scan and surgical interventions should be performed to avoid the delay of the diagnosis and treatment.